Molecular-level pictures of the phase transitions of saturated and unsaturated phospholipid binary mixtures. Issue 1 (1st December 2014) - Wu, Fu-Gen; Sun, Hai-Yuan; Zhou, Yu; Deng, Geng; Yu, Zhi-Wu
Abstract : Saturated and unsaturated lipids change nonsynchronously upon heating-induced phase transitions. Abstract : Binary lipid mixtures consisting of saturated and unsaturated lipids are important models for natural cell membranes. However, a detailed molecular picture for the phase transition process of such lipid binary mixtures remains unclear. Herein, by using deuterated dipalmitoylphosphatidylcholine (DPPC- d 62 ) and hydrogenated dioleoylphosphatidic acid (DOPA), we expect to separately analyze the changes of the two lipid components during thermotropic phase transitions by temperature-dependent Fourier transform infrared (FTIR) spectroscopy, and uncover the hidden secrets of a seemingly single endothermic peak observed in differential scanning calorimetry (DSC) experiments. We found that at low DOPA concentrations (10–20 mol%), a gel to fluid conformational transition of DPPC- d 62 and a fluidization transition of DOPA by DPPC- d 62 were observed. The two lipids were found to have nonsynchronous conformational rearrangements in the tail regions upon thermotropic phase transitions, with the change of DOPA earlier than DPPC- d 62 . Besides, in the mixed fluid phase at 40 °C, the unsaturated DOPA can be fluidized (loosened) by the saturated DPPC- d 62, and such an isothermal fluidization effect is more pronounced at elevated DPPC- d 62 concentrations. At higher DOPA contents (30–50 mol%), only DPPC- d 62 molecules have conformational transitions upon heating. The present work demonstrates for the first time that the unsaturated lipid component can have significant conformational reorganizations in the phase transition process of a saturated–unsaturated binary lipid mixture.